Investigação da produção de pensamentos contrafactuais a partir de manchetes jornalísticas sobre violência sexual - Piai, Livia Polastri (Universidade Federal de São Carlos, 2024)
Counterfactual thoughts are characterized by thinking about the past. Based on conditional logical propositions (if..., then....), they aim to modify elements of reality, imagining outcomes different from what occurred. They are mainly produced following adverse events, for which alternatives are imagined that provide better results. The study of counterfactual thoughts allows for the understanding of complex emotions, such as guilt. They have significant importance in the legal context, since, depending on the focus given by the judge or the suggestion in a lawyer's argument, the outcomes can be altered. Thus, given the importance of the comparative process for interpretations in judgment, depending on the situation to which it is compared, a crime may seem less harmful. Within the journalistic context, an exaggerated focus may be given to the victim at the expense of the aggressor in headlines about sexual violence crimes, a fact that suggests the victim's demoralization. Given the greater blame imputed to the victim, this study intends to investigate how participants elaborate counterfactuals based on journalistic articles referring to sexual violence. Twenty adults, over 18 years of age and who signed the Free and Informed Consent Form (TCLE), participated, having been recruited through invitations on social networks. The participants remotely answered a sociodemographic questionnaire and the counterfactual thinking assessment. Between 16 and 17 counterfactuals were found, all of upward direction except for two neutral ones. The target of the modification, in the headline that focused on the victims' attitudes, was mostly self-referential, and, in the one that focused on the aggressors, there were more other-referential alterations. The structure, direction, and aspects of reality altered were mostly upward, subtractive, self-referential, and with alterations related to action/inaction and obligation, a structure similar to the findings of other authors in the field.
Investigation of the production of counterfactual thoughts based on news headlines about sexual violence
Keywords: Pensamento contrafactual; Violência; Manchetes; CIENCIAS HUMANAS::PSICOLOGIA